PENGARUH PROMOSI, HARGA DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MOBIL WULING CONFERO DI SURAKARTA - Rizky Banyu Ayesa; Sri Hartono; Burhanudin Ahmad Yani (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this study are analyze the effect of promotion, price, and brand image on the decision to purchase a Wuling Confero car. This research was conducted at the Wuling Confero car dealer PT. Automobil Jaya Mandiri Surakarta. The study population was 200 consumers of Wuling Confero car brands, while the study sample was 40 people taken by area random sampling technique. The research data was taken with an instrument in the form of a questionnaire for promotion variables (X1), price (X2), brand image (X2), and purchase decision (Y). Item validity test used the product moment correlation formula and item reliability with the Alpha formula. The results of the validity and reliability of 24 questions are all valid and reliable, so that they can be used as research measurement tools. Data analysis techniques used multiple linear regression with the statistical formula t test and F test. Analysis of the research data obtained the results: 1) Analysis of multiple linear regression obtained together: Y = 1.868 + 0.464 X1 + 0.560 X2 + 0.401 X3 + e. If the three independent variables namely promotion (X1), price (X2) and brand image (X3) are positive, then the purchasing decision will increase by 1,868. If X1 is increased, while X2 and X3 are fixed, the purchasing decision will increase (positive effect). If X2 is increased, while X1 and X3 are fixed, the purchasing decision will increase. If X3 is increased, while X1 and X2 are fixed, the purchasing decision will increase. 2) Analysis of the t test of the promotion variable (X1) obtained tcount value of 2.503 > ttable value of 2.021, significance value of 0.015 < 0.05. promotion has a positive and significant effect on purchasing decisions. T test analysis of the price variable (X2) obtained tcount value of 3.252 > ttable value of 2.021, a significance value of 0.002 < 0.05, the price of a positive and significant effect on purchasing decisions. T test analysis of the brand image variable (X3) obtained tcount value of 2.401 > ttable value of 2.021, a significance value of 0.022 < 0.05, brand image has a positive and significant effect on purchasing decisions. 3) Analysis of the F test obtained Freg = 10,075 > Ftable = 3.25 significance value of 0,000 < 0.05, concluded that promotion, price, and brand image together have a positive and significant effect on purchasing decisions. The higher the promotion, price, and brand image, the higher the decision to purchase a Wuling Confero brand car in Surakarta. 4) Analysis of the R2 test obtained 0.411 results, which means that the variability of the dependent variable of purchasing decisions can be explained by the variability of the independent variables (Promotion, Price, and Brand Image) of 41.1% while the remaining 58.9% is explained by other variables not included in the regression model, among others: services, insurance, guarantees, security, comfort, bonuses, and others.